Research Needs on Native Plants of Economic Importance - Maiti, Ratikanta; Thakur, Ashok K. (International Journal of Economic Plants, 2017)
Mother Earth has gifted immense treasure of native plants to mankind that possess economic importance in one or other way. The Almighty has bestowed upon with huge biodiversity, however it is finite and diminishable. Thus, there is necessity to conserve and utilize them in a sustainable manner. Ever since the evolution of mankind various native plants, such as edible plants, medicinal plants, vegetables, fibre yielding, ornamental plants, edible fungi and others for their daily necessities, Which are overexploited and most of which are on the verge of extinction. Very little attempt has been undertaken to conserve and propagate. Few examples of such native plants have been narrated in the following text. In Northeast arid lands of Mexico, Agave lecheguilla Torr. and Yucca carnerosana (Trel) are overexploited for the production of fibres called “Ixtle” having great economic importance in arid lands of Mexico. This may lead to extinction. Similarly, wild chilli, ‘Chile piquin’ (Capscicum annum var aviculare (Dierb) is overexploited by farmers, who collect these chilies from their wild habitat...